Radial nerve palsy associated with humeral shaft fractures - Early exploration or expectant procedure? An analysis concerning current strategies of treatment Die primäre N.-radialis-Parese bei Humerusschaftfrakturen - Revidieren oder zuwarten? Eine Analyse der Versorgungsrealität in Deutschland - Grassmann, J. P.; Jungbluth, Pascal; Bullermann, L.; Hakimi, M.; Gehrmann, S. V.; Thelen, S.; Windolf, J.; Wild, M.; Betsch, Marcel (Zeitschrift für Orthopädie und Unfallchirurgie, 2010)
Background: With a prevalence from 11.8 to 18 % no fracture is as often associated with nerve damage as the humeral shaft fracture. Whether the radial nerve should be surgically explored in association with a palsy in humeral shaft fractures in order to exclude an interposition or discontinuity is being discussed controversially. The aim of this study was to assess the strategies for primary care of radial nerve palsies associated with humeral shaft fractures in Germany. Material and Methods: In a standardised survey 495 traumatological and 134 neurosurgical clinics were interviewed regarding the treatment of primary radial nerve palsies after humeral shaft fractures. The distribution of the survey included all level-one trauma centres. Statistics were based on the supply strategies, the number of observed contusions, discontinuities and inter-position of the N.radialis in the fracture gap. Moreover, the results were recorded after primary neurorrhaphy. Results: The evaluable response rate to the questionnaire was 56 % (university hospitals 77 %, level-one trauma centres 63 %, level-two trauma centres 70 %, level-three trauma centres 44 %). 6097 humeral shaft fractures have been treated per year, the incidence of primary radial nerve palsy was 8.6 %. Regarding the management strategies, 59 % of the hospitals advocated exploration of the nerve, while 25 % reported that the decision depends on the individual case. 16 % reject the exploration in case of a primary nerve palsy. In the case of an exploration, contusions (74 %) of the nerve were largely seen, followed by nerve interpositions in the fracture gap (19 %) and discontinuity (7 %). In the case of neurorrhaphy, a partial or complete remission was found in 87 % of cases. Discussion: Although a primary expectant procedure is recommended in the literature due to the high spontaneous remission rate of 90 %, an early exploration of the nerve is often preferred in clinical practice. In these cases, the use of an interlocking intramedullary nail as a minimally invasive treatment option does not appear useful due to the direct exposure of the fracture zone and the radial nerve. Interestingly, the feared discontinuity occurs rarely. The impact of nerve interposition in the fracture gap without surgical exploration remains unclear due to the lack of visibility. Conclusion: There is no consensus concerning the treatment of radial nerve palsies after humeral shaft fractures in Germany. Discontinuities are rare, the rate of spontaneous recoveries is high. Whether and when an exploration of the radial nerve is obligatory in primary radial palsy remains unclear and should be clarified by prospective randomised trials. © Georg Thieme Verlag KG Stuttgart.
CRIS-Team Scopus Importer:2022-07-20
Keywords: humeral fracture; radial nerve palsy; strategies for treatment; therapy